ETHICS IN HEALTH CARE SETTINGS: PRACTICES OF HEALTHCARE PROFESSIONALS AND PERCEPTIONS OF PATIENTS REGARDING INFORMED CONSENT, CONFIDENTIALITY AND PRIVACY AT TWO TERTIARY CARE HOSPITALS OF ISLAMABAD, PAKISTAN - Riaz, Sonia; Khan, Ejaz Ahmad; Jafar, Tariq (Journal of Ayub Medical College Abbottabad, 2017)
Background: Medical profession works within thin lines of professionalism and trust. Faith of the patients often breached but less reported among the Low and Middle-Income Countries (LMICs). In Pakistan, though the Pakistan Medical and Dental Council (PMDC) have its own code of medical ethics but there isn't much evidence on regulating ethical misconducts. Apart from the gross violations of the code of conduct, the insensible misuse of informed consent, confidentiality and privacy is very common. This study is an effort to explore practices of informed consent, confidentiality and privacy among health care providers along with assessment of perceptions of patients about ethical practices in two tertiary care hospitals of Islamabad, Pakistan. Methods: We conducted eight homogenous Focus Group Discussions (FGDs), four each in both the public and private sector hospitals till the saturation was achieved. Results: Informed consent, in clinical practice, was found not being practiced. Confidentiality was not being uniformly applied in practices. Patients perceived the practices being contrary to the ethics. According to patients, ethical measures were found satisfactory in private hospitals. However, patients were not gratified fully with both the systems of healthcare delivery. Conclusion: There is insufficient adherence to the ethical principles in clinical practice, in both public and private sector hospitals in Islamabad, Pakistan. Informed consent, privacy and confidentiality are time and time again unheeded due to lack of robust system of monitoring and penalties by the responsible authorities. Keywords: Medical examination; Discretion; Hospitals; Medical ethics